The new 'twice migrants': motivations, experiences and disillusionments of Italian-Bangladeshis relocating to London. Issue 11 (18th August 2019) - Della Puppa, Francesco; King, Russell
ABSTRACT: Taking our cue from an earlier study of East African Asians who 'onward-migrated' to the UK in the 1960s and 1970s, this paper looks at the more recent phenomenon of Bangladeshi immigrants in Italy who are onward-migrating to London. We seek to answer three questions. First, why does this migration occur? Second, how does the ethnic group we call 'Italian-Bangladeshis' narrate their working lives in London and to what extent do they feel 'at home' there? Third, what are the gaps between their expectations held before the move and the actual social and economic conditions they encounter in London? Empirical evidence comes from 40 in-depth interviews with Italian-Bangladeshis who have already onward-migrated or plan to. Most Italian-Bangladeshis move to London to escape socially limiting factory work in Italy, to invest in the educational future of their children, and to join the largest Bangladeshi community outside of their home country. In London, they describe feeling more 'at home' than in Italy, due to the size and multiple facilities of the Bangladeshi community, their lack of 'visibility' and of racialisation, and the greater sense of religious freedom. But their onward-migration experience has its more negative sides: the inability to access more than low-paid casual work in London's service economy, the cost of housing, and the difficulty of making social contacts beyond their ethnic community, especially with those they regard as 'natives', i.e. 'white' British.